Implementation of Advanced Battery Technologies for Electric Mobility, Renewable Energy Storage, and Electronic Devices Using the Topsis Method - AKKARI, MUHAMMED (İstanbul Kültür Üniversitesi, 2024)
Solid-state batteries are poised to revolutionize multiple industries, especially electric vehicles, renewable energy storage, and small devices such as smartphones and wearables. This is due to the increased demand for energy storage systems after the enactment of environmental conservation laws and the safety problems in current lithium-ion batteries. Unlike current lithium-ion batteries that use liquid electrolytes, solid-state batteries utilize a solid electrolyte material. This study aims to identify the best type of all-solid-state battery using the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method, comparing three alternatives: polymer-based, sulfide-based, and oxide-based solid batteries. Six key criteria were considered: cost, efficiency, lifetime, safety, energy densities, and ionic conductivity. Although the researches and studies about all solid state batteries are still rare. Each criterion was carefully evaluated to ensure a thorough assessment. The TOPSIS method was then applied to rank the battery types based on their relative closeness to an ideal solution. Although more studies are needed to enhance the efficiency and capacity of solid-state batteries to compete with current batteries with liquid electrolytes, the results indicate that sulfide-based solid-state batteries are the ideal option, demonstrating the most favorable balance across all evaluated criteria. This suggests that sulfide-based batteries have significant potential to drive advancements in energy storage technology. By excelling in crucial areas such as efficiency and safety while maintaining reasonable costs and minimal ionic conductivity, sulfide-based solid-state batteries stand out as a promising solution for the future of energy storage across various applications.
Topsıs Yöntemi Kullanılarak Elektrikli Mobilite, Yenilenebilir Enerji Depolama Ve Elektronik Cihazlara Yönelik İleri Pil Teknolojilerinin Uygulanması
Yüksek lisans tezi.
Keywords: Solid-state Batteries; Renewable Energy Storage; Polymer-based Solid Batteries; Oxide-based Solid Batterie